Growth/differentiation factor 15 controls ependymal and stem cell number in the V-SVZ - Baur, Katja; Carrillo García, Carmen; Şan, Şeydanur; Hahn, Manja von; Strelau, Jens; Hölzl-Wenig, Gabriele; Mandl, Claudia; Ciccolini, Francesca (Stem cell reports, 2024)
The expression of growth/differentiation factor (GDF) 15 increases in the ganglionic eminence (GE) late in neural development, especially in neural stem cells (NSCs). However, GDF15 function in this region remains unknown. We report that GDF15 receptor is expressed apically in the GE and that GDF15 ablation promotes proliferation and cell division in the embryonic GE and in the adult ventricular-subventricular zone (V-SVZ). This causes a transient generation of additional neuronal progenitors, compensated by cell death, and a lasting increase in the number of ependymal cells and apical NSCs. Finally, both GDF15 receptor and the epidermal growth factor receptor (EGFR) were expressed in progenitors and mutation of GDF15 affected EGFR signaling. However, only exposure to exogenous GDF15, but not to EGF, normalized proliferation and the number of apical progenitors. Thus, GDF15 regulates proliferation of apical progenitors in the GE, thereby affecting the number of ependymal cells and NSCs.